Oriental Policies and Investment Prospects Increasing the Economic Development Capacity in Republic of Kosovo - Dumi, Alba; Kiser, Ilirjana; Karakushi, Avni (Richtmann Publishing, 2012)
In order to develop the economy in most organized and desirable achievements outcomes is required the greatest efficiency ofthe organizing institution in the investment advisory. By this context, state institutions, professional institutes and other mechanisms ofcivil government should be active in the development policies orientation, as well as engaged in the design of economic investmentprojects. Besides other financial resources, great investment potential and our workers are employed abroad. Hence, owners who havea long time in Western Developed Countries, the experience gained and the financial savings budget are considerably potential that theircapital engaged in various productive activities, which will enable economic development on the one hand, to increase the financialpotential and on the other hand their financial remittances dedicated to their families, serve not only to meet the basic needs, but also toincrease business development; While those who invested in the economy at large led to the trade development ,although thecircumstances were difficult they invested in manufacturing. Today the benefits of different countries, financial institutions and the laborforce concentrated in the â€Diaspora-Immigrationâ€ Kosovo investitures that are living in developing countries, are great potential toinfluence economic development in general and the development of private initiative in particular. According to these conditions shouldbe taken into account the importance on financial orientation of those economic activities which are long-term perspective.